PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU - Novi Yulianti Yulianti (STKIP Subang, 2022)
This study aims to determine the effect of the problem based learning model on the learning outcomes of the sub theme of my nation's cultural diversity. The type of research used is a quasi-experimental design using a nonequivalent control group design. This research was conducted in Ciomas 06 State Elementary School, Bogor Regency, Class IVA, and IVB as the experimental class and control class. The data from this study were analyzed using Microsoft Excel 2016. Data collection to obtain student learning outcomes tests was obtained using pretest and posttest. The data analysis technique in this study used the t-test. Based on the results of data analysis from hypothesis testing using t-test obtained tcount = 18.71368, while ttable at a significant level /2 = 0.025 of 2.00324, then obtained tcount> ttable that is 18.71368> 2.00324 so Ha is accepted or H0 is rejected. Thus, there is an effect of the problem based learning model on the learning outcomes of the sub-theme of cultural diversity of my people in the fourth grade students of SDN Ciomas 06.